Lymphadenopathy after the Anti-COVID-19 Vaccine: Multiparametric Ultrasound Findings - Giulio Cocco; Andrea Delli Pizzi; Stefano Fabiani; Nino Cocco; Andrea Boccatonda; Alessio Frisone; Antonio Scarano; Cosima Schiavone (Biology, 2021)
Background: Post-anti-COVID-19 vaccine lymphadenopathy has recently been described in the literature. In this study, we investigated the multiparametric US findings of patients with post-vaccine lymphadenopathy and compared these findings among different anti-COVID-19 vaccines. Methods: We retrospectively evaluated 24 patients who underwent US between January and May 2021 due to post-anti-COVID-19 lymphadenopathy. The presence, size, location, number, morphology, cortex-hilum, superb microvascular imaging (SMI) and elastosonography of lymph nodes were assessed. Descriptive statistics were calculated and differences among anti-COVID-19 vaccines were analyzed using the Kruskal–Wallis test. A p-value ≤ 0.05 was considered statistically significant. Results: Sixty-six nodes were assessed. They were axillary (mean 1.6 cm ± 0.16) in 11 patients (45.8%) and supraclavicular (mean 0.9 cm ± 0.19) in 13 patients (54.2%). In 20 patients (83.3%), the number of nodes was ≤3. Prevalent US features included oval morphology (18, 75%), asymmetric cortex with hilum evidence (9, 37.5%), central and peripheral vascular signals (12, 50%) at SMI and elastosonography patterns similar to the surrounding tissue (15, 71.4%). No significant differences among the three anti-COVID-19 vaccines were observed (p > 0.05). Conclusions: Anti-COVID-19 vaccines may present lymphadenopathy with “worrisome” US features regarding size, shape, morphology, cortex-hilum, SMI and elastosonography. An awareness of the patient’s history and US findings may help in the early recognition of this clinical scenario and in the appropriate selection of patients for a short-term US follow-up.